Rehabilitation of Mandibular Dentition Under Conscious Sedation in A Pediatric Patient: a case report - Khandakar Nuruzzaman; Anam Ahmed; Huda Mannan (Update Dental College, 2022)
Behavior management of younger children during dental treatment always has been a major challenging task for a pediatric dentist. The requirement of advanced behavior guidance techniques in the management of lacking cooperative behavior child is undeniable. Conscious sedation is considered to be one of the best suitable methods for delivering dental treatment in younger children. The procedure exhibits multiple advantages like extensive treatment in a single visit, aids in delivering optimum dental treatment, and prevention of developing psyche of a child. The combined use of pharmacological agents increases the potency of sedation as well as is associated with an analgesic, anxiolytic and amnestic effect. This report represents the first dental pediatric conscious sedation case in Bangladesh in 5.5 years old, anxious, and lacking cooperative behavior child. Update Dent. Coll. j: 2022; 12(1): 37-39